Chromosomal radiosensitivity in South African breast cancer patients before and after radiotherapy - Muller, Xanthene (My University, 2013)
Introduction: Radiosensitivity (RS) of South African women with breast cancer was investigated as it has been studied in European women, but to date this has not been studied in South African women. The micronucleus assay was used to determine the amount of DNA damage on lymphocytes of breast cancer patients. Materials and Methods: The first component to this study involved the collection of blood samples from breast cancer patients and healthy individuals. For the second component, blood samples from breast cancer patients were collected before and after the completion of radiotherapy (RT). A centromeric micronucleus assay using the Fluorescent in situ Hybridisation (FISH) pancentromeric probe was used to investigate the origin of the micronuclei (MN) and to distinguish between radiation-induced [centromere negative (CM-)] and spontaneous [centromere positive (CM+)] MN. Results: Micronucleus frequencies were slightly higher in breast cancer patients than those observed in lymphocytes of healthy donors. This was noted for the different radiation doses and indicated a trend towards an enhanced chromosomal radiosensitivity in this cancer population. Results were compared before and after radiotherapy. The micronucleus scores for the 0 Gy (sham irradiated samples) were significantly higher (p < 0.05) post radiotherapy. This is an expected result as ionising radiation causes more damage. However, blood samples from post-therapy patients, were shown to have fewer MN after subsequent in vitro 2 Gy and 4 Gy irradiation respectively. When assessing the centromeric micronucleus assay results, a significantly (p < 0.05) higher number of CM- MN was observed than CM+ MN after RT, thereby indicating that ionising radiation causes more breaks in the chromosomes (clastogenic damage). Discussion and Conclusion: This study demonstrates that a group of South African breast cancer patients have slightly higher micronucleus frequencies compared to a population of healthy women, indicating a trend towards a higher sensitivity to radiation.
Keywords: Breast Neoplasms; Radiotherapy